ANALYSIS OF THE METHODOLOGICAL APPROACH OF STRENGTHENING OF INTERNATIONAL ECONOMIC SECURITY - Іlienko, Оksana (Proceedings of National Aviation University (archive), 2013)
The article analyzes the methodological approach of strengthening of international economic security as the main direction of achieving high economic results in the modern conditions of active expansion of globalization processes in the world economic system.